Improving Environmental Performance in Corporations Using Green Human Resource Management - Mutmainah, Rouf Esa; Lestari, Nadya Mega Dwi; Andriyani, Andriyani; Darmastuti, Ismi (LifeSciFi, 2025)
Organizations involved in improving environmental performance are increasingly prioritizing Green Human Resource Management. As awareness growing with positive impact of business activities on environmental sustainability, companies face challenges in implementing Green Human Resource Management practices. Green Human Resource Management (GHRM) concept involves integrating environmental considerations into Human Resources (HR) policies, with the aim of encouraging the use of sustainable resource use and increase environmental awareness within the organization. It aims to engage employees in environmentally supportive practices, raise awareness of environmental issues, and strengthen a culture of sustainability. This research uses the literature review method on Green Human Resource Management, which includes various types of literature on the topic. The purpose of this study is to analyse the influence of Green Human Resource Management in increase environmental performance in the company. The outcome is a positive impact that the Green Training, and Involvement on Corporate Environmental Performance.